Tenun Dan Penerapannya pada Desain Interior sebagai Warisan Budaya yang Memiliki Nilai Jual yang Tinggi - Grace Hartanti (Bina Nusantara University, 2011)
Weaving is one of the traditional fabric cultural arts of Indonesia produced in various regions across the archipelago (Sumatra, Kalimantan, Bali, Sulawesi, Lombok, Sumbawa, etc.). Weaving has a significance, historical value, and high technique both in terms of colors, patterns, materials and type of yarn used and each region has the characteristics of each. Weaving as one of high cultural heritage (Heritage) is the pride of Indonesia which may reflect national identity. Therefore, weaving both in terms of production engineering, design and the resulting product should be maintained and preserved its existence, and promoted for reuse. One of them in the world of interior design can be used as an aesthetic element to promote local cultural elements (local content) of Indonesia.